Identification of clinical, epidemiological and laboratory risk factors for leprosy reactions during and after multidrug therapy - Antunes, Douglas Eulálio (Instituto Oswaldo Cruz, Ministério da Saúde, 2013)
This cross-sectional retrospective study evaluated 440 leprosy patients; 57% (251/440) had leprosy reactions during and/or after multidrug therapy, 80.5% (202/251) of whom presented with multibacillary leprosy. At diagnosis, positive bacterial index (BI) [odds ratio (OR) = 6.39; 95% confidence interval (CI): 4.1-10.1)] or polymerase chain reaction (PCR) (OR = 9.15; 95% CI: 5.4-15.5) in skin smears, anti-phenolic glycolipid-1 (anti-PGL-1) ELISA (OR = 4.77; 95% CI: 2.9-7.9), leucocytosis (OR = 9.97; 95% CI: 3.9-25.7), thrombocytopenia (OR = 5.72; 95% CI: 2.3-14.0) and elevated lactate dehydrogenase (OR = 2.38; 95% CI: 1.4-4.0) were potential markers for the development of reactions during treatment. After treatment, positive BI (OR = 8.47; 95% CI: 4.7-15.3) and PCR (OR = 6.46; 95% CI: 3.4-12.3) in skin smears, anti-PGL-1 ELISA (OR = 2.25; 95% CI: 1.3-3.9), anaemia (OR = 2.36; 95% CI: 1.2-4.5), leucocytosis (OR = 4.14; 95% CI: 1.5-11.6) and thrombocytopenia (OR = 3.70; 95% CI: 1.3-2.2) were risk factors for the occurrence of reactions during the study period. The identification of groups with an increased risk for developing reactions will allow for the timely development of a treatment plan to prevent nerve damage and, therefore, the appearance of the disabling sequelae associated with the stigma of leprosy.